Immunological Balance Is Associated with Clinical Outcome after Autologous Hematopoietic Stem Cell Transplantation in Type 1 Diabetes - Malmegrim, Kelen C. R.; de Azevedo, Júlia T. C.; Arruda, Lucas C. M.; Abreu, Joana R. F.; Couri, Carlos E. B.; de Oliveira, Gislane L. V.; Palma, Patricia V. B.; Scortegagna, Gabriela T.; Stracieri, Ana B. P. L.; Moraes, Daniela A.; Dias, Juliana B. E.; Pieroni, Fabiano; et al. (Frontiers in Immunology, 2017)
Autologous hematopoietic stem cell transplantation (AHSCT) increases C-peptide levels and induces insulin-independence in patients with type 1 diabetes. This study aimed to investigate how clinical outcomes may associate with the immunological status, especially concerning the balance between immunoregulation and autoreactivity. Twenty-one type 1 diabetes patients were monitored after AHSCT, and assessed every six months for duration of insulin independence, C-peptide levels, frequencies of islet-specific autoreactive CD8+ T-cells, regulatory lymphocyte subsets, thymic function and T-cell repertoire diversity. In median follow-up of 78 (range 15-106) months, all patients became insulin-independent, resuming insulin after median of 43 (range 6-100) months. Patients were retrospectively divided into short- or prolonged-remission-groups, according to duration of insulin independence. For the entire follow-up, CD3+CD4+ T-cell numbers remained lower than baseline in both groups, whereas CD3+CD8+ T-cell levels did not change, resulting in a CD4/CD8 ratio inversion. Memory CD8+ T-cells comprehended most of T-cells detected on long-term follow-up of patients after AHSCT. B-cells reconstituted to baseline levels at 2-3 months post-AHSCT in both patient groups. In the prolonged-remission-group, baseline islet-specific T-cell autoreactivity persisted after transplantation, but regulatory T-cell counts increased. Patients with lower frequencies of autoreactive islet-specific T-cells remained insulin-free longer and presented greater C-peptide levels than those with lower frequencies of these cells. Therefore, immune monitoring identified a subgroup of patients with superior clinical outcome of AHSCT. Our study shows that improved immunoregulation may balance autoreactivity endorsing better metabolic outcomes in patients with lower frequencies of islet-specific T-cells. Development of new strategies of AHSCT is necessary to increase frequency and function of T and B regulatory cells and decrease efficiently autoreactive islet-specific T and B memory cells in type 1 diabetes patients undergoing transplantation.